LAJU DEKOMPOSISI AWAL SERASAH POHON Palaquium obovatum, Spathodea campanulata dan Calophyllum soulattri DI HUTAN BRON WAREMBUNGAN KABUPATEN MINAHASA - Rumambi, Juwita F.; Langi, M. A.; Nurmawan, Wawan (Universitas Sam Ratulangi, 2018)
ABSTRACTÂ The availability of nutrient inputs for soil fertility in forests is very important to preserve in an effort to anticipate a decrease in land productivity. Litter decomposition is a process of destruction of organic matter (litter) into nutrients available in the soil. This study aims to determine and compare the rate of decomposition of Palaqium obovatum, Spathodea campanulata, and Calophyllum soulattri litter in Bron Warembungan Forest, Minahasa Regency. This study was carried out on the leaf litter of Palaqium obovatum, Spathodea campanulata, and Calophyllum soulattri. The method of decomposition rate data collection using 36 litter bags placed randomly (with experiments using a completely randomized design (CRD) with two factors namely tree type and duration of decomposition) on the forest floor taken every week for four weeks, followed simultaneously with temperature measurements and humidity. The results showed that of the three main tree species in Bron Forest, the highest decomposition rate was shown by leaf litter of Spathodea campanulata with an average of 15.49% per week, followed by Palaquium obovatum (11.74% per week) and then Calophyllum soulattri ( 3.07% per week). The decomposition process in the three leaf litter took place very quickly in the first week which can also be associated with the results of measurements of water content in litter.Keywords: tropical rainforest, decomposition of litter, leaf litter